The poetics of protest : literary form and political implication in the victim-of-society novel - Goodin, George (Southern Illinois University Press, 1985)
Goodin takes a formalistic approach to political expression in the victim-of-society novel, asking the question, how do the formal features of the novel constrain thematic expression? He notes that the writer must balance the protagonist's role as victim against the role as resilient human being capable of dealing with his or her problems. If the protagonist is too strong, both help and reform become unnecessary; if too weak, the situation becomes hopeless, thus limiting the power and appeal of the work as art and as political protest. Goodin offers a schema of different types of victims: the innocent, the virtuous, the flawed, and the pseudo, examining twenty different novels. He concludes by examining the options the writers have with respect to the character and fate of their protagonists. Hewing to a rather old-fashioned insistence on the interaction between the text and society, Goodin suggests that even though imperfect, these novels probably have decreased the amount of injustice in the real world.